2001
DOI: 10.1038/35084005
|View full text |Cite
|
Sign up to set email alerts
|

Neurophysiological investigation of the basis of the fMRI signal

Abstract: Functional magnetic resonance imaging (fMRI) is widely used to study the operational organization of the human brain, but the exact relationship between the measured fMRI signal and the underlying neural activity is unclear. Here we present simultaneous intracortical recordings of neural signals and fMRI responses. We compared local field potentials (LFPs), single- and multi-unit spiking activity with highly spatio-temporally resolved blood-oxygen-level-dependent (BOLD) fMRI responses from the visual cortex of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

244
3,933
33
53

Year Published

2002
2002
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 5,683 publications
(4,263 citation statements)
references
References 44 publications
244
3,933
33
53
Order By: Relevance
“…A relative increase in theta oscillations could therefore lead to a decrease in the BOLD signal. Simultaneous recording of hemodynamic responses and intracortical electrophysiological responses in the visual cortex of cat (Niessing et al, 2005) and monkey (Logothetis et al, 2001;Shmuel et al, 2006) corroborate this notion. In the cat, Niessing et al (2005) reported negative correlations in between lower frequencies (delta and theta) and the hemodynamic responses, and strong positive correlations with gamma band activity during visual stimulation.…”
Section: Discussionsupporting
confidence: 58%
“…A relative increase in theta oscillations could therefore lead to a decrease in the BOLD signal. Simultaneous recording of hemodynamic responses and intracortical electrophysiological responses in the visual cortex of cat (Niessing et al, 2005) and monkey (Logothetis et al, 2001;Shmuel et al, 2006) corroborate this notion. In the cat, Niessing et al (2005) reported negative correlations in between lower frequencies (delta and theta) and the hemodynamic responses, and strong positive correlations with gamma band activity during visual stimulation.…”
Section: Discussionsupporting
confidence: 58%
“…The post‐stimulus PnormaltO2 overshoot is known to be uncoupled from metabolic demand (Leithner & Royl, 2014) and is determined by increases in local synaptic activity itself and the ability of the neurovascular unit to respond to increases in synaptic transmission (Logothetis et al . 2001). However, previous studies have shown that preconstriction of the cerebral vasculature can enhance the BOLD response evoked by somatosensory stimulation (Mulderink et al .…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between BOLD signals and excitatory neuro‐metabolic processes has been studied extensively; however, the relationship between BOLD signals and inhibitory neuro‐metabolic processes is less well understood 3, 4, 5. One of the key inhibitory metabolites is γ‐aminobutyric acid (GABA), which is the main inhibitory neurotransmitter of the brain and is believed to have a direct impact on BOLD contrast through regulation of neuronal firing rates 6, 7, 8. In the human brain in vivo , the relationship between GABA and BOLD signals has been investigated in studies that combined fMRI and MRS 7, 9, 10, 11, 12, 13, 14, 15…”
Section: Introductionmentioning
confidence: 99%